ANALISIS PENGARUH PROFITABILITAS, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP KETEPATAN WAKTU PELAPORAN KEUANGAN - Shinta Kasin, Rizka Indri Arfianti (Jurnal Akuntansi, 2018)
Timeliness of financial reporting aims to provide information on the financial position, performance, and changes in the company's financial position on time before losing its ability in economic decision-making. The information in the financial statements is said to be useful when available on time when needed. The purpose of this study is to determine the effect of profitability, leverage, and company size on timeliness. The research method used is logistic regression analysis method. The sampling technique used is purposive sampling method. The samples used are 87 manufacturing companies listed on the BEI in 2014-2016 with a total of 261 data. The analysis used in this study using SPSS version 20. The results showed that profitability had a significant positive effect on timeliness at α = 5% with p-value of 0.0275, leverage did not significantly influence p-value value 0.4995, and firm size also no significant effect on timeliness with p-value of 0.350. The conclusion of this study is that there is sufficient evidence that companies with high profitability tend to be timely in delivering financial statements and there is not enough evidence of companies that have low leverage and small company size tend to be timely in delivering financial statements. Keywords: Timeliness, Profitability, Leverage, Firm Size